Imaging of hydroxyl radical (·OH) distributions using luminol water during irradiation with low-energy X-rays. (1st October 2022) - Yamamoto, Seiichi; Yabe, Takuya; Hirano, Yoshiyuki; Kataoka, Jun
Abstract: Reactive hydroxyl radicals (·OH) play important roles in the biological effects of radiation exposure or radiation therapy, and the distribution of ·OH in water during irradiation is of interest to researchers. However, real-time ·OH distribution measurement during irradiation has so far not been achieved due to the difficulty of detecting ·OH. To make these distribution measurements possible, we attempted the imaging of light emitted from luminol water during irradiation with low-energy X-rays. Imaging of the light emitted from luminol water was conducted using a cooled charge-coupled device (CCD) camera during X-ray irradiation to luminol water at lower energy than the Cherenkov-light threshold. The light emission of luminol water was 25 times higher than that of water, and clear images of light distributions were measured for the luminol water. By carrying out the imaging of luminol water with the addition of a radical scavenger to the luminol water, we could confirm that the emitted light was from ·OH produced in water. With this addition of the radical scavenger, the light intensity decreased as the weight of the scavenger increased. With these results, we confirmed that the detected light distribution in luminol water could be attributed to the ·OH produced by the X-ray irradiation.